Blocking Tim-3 enhances CD8+ T cell activity to inhibit hepatocellular carcinoma recurrence post-radiofrequency ablation - Na Wu; Xinru Pei; Weiguo Cai; Xiaodie Ye; Wei Lu (International Journal of Hyperthermia)
Background Incomplete radiofrequency ablation (iRFA) for hepatocellular carcinoma (HCC) during radiofrequency ablation (RFA) may result in rapid progression of residual tumors and resistance to anti-PD-1 therapy. Research has demonstrated elevated T-cell immunoglobulin and mucin domain 3 (Tim-3) expression in CD8+ T cells in the peripheral blood of patients with HCC after RFA, leading to a diminished anti-tumor immune response. Therefore, this study examined the effectiveness of anti-Tim-3 therapy in treating residual tumors after iRFA and explored the underlying mechanisms.Methods To examine the expression of Tim-3 in the residual tumors after iRFA for HCC in mice. Treat residual tumors with anti-αTim-3 and evaluate its efficacy. Transcriptomic sequencing was conducted on the residual tumors to explore the underlying mechanisms. Meanwhile, residual tumors were treated with a combination of anti-αTim-3 and anti-αPD-1 to evaluate efficacy.Results This study demonstrated elevated Tim-3 expression in CD8+ T cells within residual tumors after iRFA. CD8+ T cells exhibit attenuated anti-tumor immune responses associated with accelerated tumor progression. Treatment with anti-αTim-3 impeded the advancement of residual tumors by enhancing CD8+ T cell infiltration and stimulating their anti-tumor activities. Furthermore, anti-αTim-3 therapy upregulated PD-1 expression in residual tumors. Combination therapy involving anti-αTim-3 and anti-αPD-1 elicited a robust anti-tumor immune response.Conclusions Tim-3 expression is elevated in CD8+ T cells within residual tumors after iRFA, which contributed to their accelerated advancement. Anti-αTim-3 slows tumor progression by boosting CD8+ T cell anti-tumor activity and enhancing response to anti-αPD-1 treatment.